2020
DOI: 10.1002/cmdc.201900533
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Discovery of N,N’‐Carbazoyl‐aryl‐urea Inhibitors of Zika NS5 Methyltransferase and Virus Replication

Abstract: The recent outbreaks of Zika virus (ZIKV) infection worldwide make the discovery of novel antivirals against flaviviruses a research priority. This work describes the identification of novel inhibitors of ZIKV through a structure‐based virtual screening approach using the ZIKV NS5‐MTase. A novel series of molecules with a carbazoyl‐aryl‐urea structure has been discovered and a library of analogues has been synthesized. The new compounds inhibit ZIKV MTase with IC50 between 23–48 μM. In addition, carbazoyl‐aryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Previous studies have reported inhibitors of the zika virus replication/NS5-RNA-dependent RNA polymerase and/or NS5-methyltransferase ,, ,,, using various strategies. This study identified some derivatives of the said parent compounds as potential inhibitors of the virus NS5 protein, and a previous report had validated N -[4-[6- tert -butyl-5-methoxy-8-(6-methoxy-2-oxo-1 H -pyridin-3-yl)-3 quinolyl] phenyl] methanesulfonamide (PubChem identifier: CID 49835560), a derivative of dasabuvir, against hepatitis C virus NS5B polymerase but not zika virus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported inhibitors of the zika virus replication/NS5-RNA-dependent RNA polymerase and/or NS5-methyltransferase ,, ,,, using various strategies. This study identified some derivatives of the said parent compounds as potential inhibitors of the virus NS5 protein, and a previous report had validated N -[4-[6- tert -butyl-5-methoxy-8-(6-methoxy-2-oxo-1 H -pyridin-3-yl)-3 quinolyl] phenyl] methanesulfonamide (PubChem identifier: CID 49835560), a derivative of dasabuvir, against hepatitis C virus NS5B polymerase but not zika virus.…”
Section: Resultsmentioning
confidence: 99%
“…However, 1e showed equivalent binding energy of −6.675 ± 0.05 kcal/mol and K i of 12.67519392 ± 1.115312 μM for RNA-dependent RNA polymerase, while 4e showed equivalent binding energy of −7.6 ± 0.00 kcal/mol and K i of 2.648363028 ± 0.000000 μM for NS5-methyltransferase when compared with efavirenz, 3e, (−6.60 ± 0.00 kcal/mol and 14.34816176 ± 0.000000 μM for RNA-dependent RNA polymerase; −7.43 ± 0.05 kcal/mol and 3.568824547 ± 0.288630 μM for NS5-methyltransferase) (Supporting Information 1). Previous studies have reported inhibitors of the zika virus replication/NS5-RNA-dependent RNA polymerase and/or NS5-methyltransferase 2,13,[15][16][17][18][19]36,47,48 using various strategies. This study identified some derivatives of the said parent compounds as potential inhibitors of the virus NS5 protein, and a previous report had validated N- [4-[6-tert-butyl-5methoxy-8-(6-methoxy-2-oxo-1H-pyridin-3-yl)-3 quinolyl] phenyl] methanesulfonamide (PubChem identifier: CID 49835560), a derivative of dasabuvir, against hepatitis C virus NS5B polymerase 44 but not zika virus.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZIKV NS5 methyltransferase is an important target in screening for new molecules that have an inhibitory effect on the action of this enzyme, as reported in previous studies who identified the molecules ZINC1652386 [55], and N, N'-Carbazoyl-aryl-urea [56], both as target molecules for the development of anti-ZIKV drugs. In rational drug planning, the "rule of five" (ROF) by Lipinski and coauthors [29] is often used to delimit the space of compounds with the greatest number of conditions satisfied to be an oral drug.…”
Section: Resultsmentioning
confidence: 86%
“…In 2019, Caruso et al published a review article about carbazole derivatives with antiviral activity [118]. Just to supplement this excellent review, at the end of 2019, Spizzichino et al presented a series of novel molecules based on a carbazoyl-aryl-urea structure which were potent Zika virus NS5 methyltransferase able to suppress virus replication [119]. SAR studies led to the creation of compound 74 as the most active inhibitor of ZIKV-NS5MTase with IC 50 = 23 µM in an enzyme-based assay.…”
Section: Carbazolementioning
confidence: 99%